MicroRNA-29a plays a suppressive role in non-small cell lung cancer cells via targeting LASP1 - Hu, Zhaolan (Onco Targets Ther, 2016)
MicroRNA (miR)-29a has been implicated in non-small cell lung cancer (NSCLC), but the mechanism remains largely unclear. LASP1, a cAMP- and cGMP-dependent signaling protein, was recently found to promote proliferation and aggressiveness in NSCLC. However, the regulatory mechanism of LASP1 expression in NSCLC, as well as the relationship between LASP1 and miR-29a, has never been previously studied. In this study, we found that miR-29a was remarkably downregulated and low expression of miR-29a was associated with the malignant progression of NSCLC. Moreover, the expression of LASP1 was markedly increased in NSCLC tissues and cell lines. Bioinformatics analysis and luciferase reporter assay data further identified LASP1 as a target gene of miR-29a, and the expression of LASP1 was negatively mediated by miR-29a at the post-transcriptional level in NSCLC cells. Overexpression of miR-29a reduced the proliferation, migration, and invasion of NSCLC cells, just as the effects of LASP1 knockdown. Moreover, overexpression of LASP1 attenuated the suppressive effect of miR-29a on the malignant phenotypes of NSCLC cells. In addition, upregulation of miR-29a decreased the growth of A549 cells in nude mice and protected the animals from tumor-induced death. Therefore, we demonstrate that miR-29a plays a suppressive role in NSCLC via targeting LASP1, suggesting that the miR-29a/LASP1 axis may become a promising therapeutic target for NSCLC.